PERANAN KEPALA SEKOLAH DALAM MENGIMPLEMENTASIKAN MANAJEMEN BERBASIS SEKOLAH - Elfitriani, Elfitriani; Ramanda, Fatma (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is based on issues with the implementation of School-Based Management (SBM) which has not yet been fully operational. The aim of this study is to analyze and describe the role of school principals in implementing school-based management and the function of school principals in the implementation of school-based management. The method used in this article is a literature study (Library research). The data collection technique involves understanding and studying theories from various literatures. The data processing technique uses the methods proposed by Miles and Huberman, which consist of Data Collection, Data Reduction, Data Display, and Conclusion Drawing/Verification. The results of the study show that (1) the role of the school principal in the context of SBM in schools is as a driving force for school life. Through the SBM program in improving the quality of education, the school principal has several roles: (1) as a Manager, (2) as an Administrator, (3) as a Leader, (4) as an Educator, and (5) as a Supervisor. (2) In implementing SBM, the school principal creates a vision, mission, goals, and targets using the existing ones, but if there are changes, they are made through consensus. Similarly, in decision-making. The development of academic and non-academic quality improvement programs is carried out by their respective fields and they are responsible for their implementation so that everyone can know. The implementation is supported by committees and the business world, with the expectation that the school can be independent and all activities can be accounted for.